Wear-resistant dental resin composite material and preparation method thereof
Patent Information
- Application Number
- CN202611241227.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]现有口腔用耐磨与结构增强材料,多通过添加硬质填料、交联改性或表面强化等方式,提升初始力学强度与耐磨性,但在口腔长期服役过程中,材料中的有效耐磨相与基体界面易被水分子渗透,在酸性介质作用下发生水解与腐蚀,从而导致材料力学性能与耐磨性能快速衰减,表面粗糙度上升、磨损量增大
[0030]1、本发明通过合成氟掺杂锆质耐磨填料与十三氟辛基三甲氧基硅烷界面改性,显著提升牙科树脂在口腔酸性、酶解、温度循环及动态磨损复合环境下的界面稳定性与耐老化能力,解决了传统材料填料-树脂界面易被水渗透、酸性水解、酶解侵蚀导致力学与耐磨性能快速衰减的问题,相较于对照例90d老化后压缩强度衰减28.79%、挠曲强度衰减27.78%,本发明实施例力学强度衰减仅2-6%,界面结合牢固。
Smart Images

Figure SMS_6
Abstract
Description
Technical Field
[0001] This invention relates to the field of dental resin technology, and more specifically to a wear-resistant dental resin composite material and its preparation method. Background Technology
[0002] The oral cavity serves as the service environment for dental restorative materials, dentures, orthodontic appliances, and other products. It possesses complex physicochemical and biological characteristics, including aerobic conditions, high humidity, continuous acidic fluctuations, and multiple enzymatic degradation. Saliva, plaque metabolism, and food fermentation collectively form a dynamic acidic microenvironment, which also contains various biological enzymes such as esterases, proteases, and matrix metalloproteinases. These enzymes, combined with chewing abrasion and temperature cycling, continuously erode the materials.
[0003] Existing dental wear-resistant and structural reinforcement materials mostly improve initial mechanical strength and wear resistance by adding hard fillers, cross-linking modification, or surface strengthening. However, during long-term service in the oral cavity, the effective wear-resistant phase in the material and the matrix interface are easily penetrated by water molecules, and hydrolysis and corrosion occur under the action of acidic media. This leads to a rapid decline in the mechanical properties and wear resistance of the material, an increase in surface roughness, and an increase in wear.
[0004] In addition, some people in clinical practice prefer to drink carbonated beverages, acidic fruit juices, vinegar, and acidic snacks, which further reduces the local pH value in the oral cavity, enhances the acidic corrosion effect, significantly accelerates material degradation and interface damage, and, combined with the chewing wear effect, makes the wear resistance decline and structural deterioration more prominent, making it difficult to meet the needs of long-term clinical use.
[0005] Based on this, the present invention designs a wear-resistant dental resin composite material and its preparation method to solve the above problems. Summary of the Invention
[0006] To address the aforementioned shortcomings of existing technologies, this invention provides a method for preparing a wear-resistant dental resin composite material, comprising the following steps:
[0007] S1: Weigh 40-60 parts by weight of bisphenol A glycidyl methacrylate, 20-35 parts by weight of polyurethane dimethacrylate and 10-20 parts by weight of polyethylene glycol dimethacrylate, stir under light-proof and nitrogen protection, add 0.01-0.05 parts by weight of 2,2,6,6-tetramethylpiperidine-1-oxy free radical, and continue stirring to obtain the base resin solution;
[0008] S2: By weight, mix 2-5 parts of tridecafluorooctyltrimethoxysilane and 95-98 parts of ethanol aqueous solution, adjust the pH to 4.0-5.5, and mix to obtain silane coupling modified solution;
[0009] S3: Weigh out 30-45 parts by weight of zirconium oxychloride octahydrate, 0.5-3.5 parts by weight of sodium fluoride, 8-15 parts by weight of citric acid, 5-10 parts by weight of urea and 100-150 parts by weight of deionized water.
[0010] Citric acid and urea were added to deionized water in sequence and stirred. Zirconium oxychloride octahydrate was added and stirred. Sodium fluoride was added in 3-5 portions and stirred continuously to obtain the precursor mixture.
[0011] The precursor mixture was subjected to a closed hydrothermal reaction at 160-200℃, cooled and centrifuged to obtain solid product A, washed and dried to obtain precursor powder, calcined at 350-450℃ and cooled to obtain fluorine-doped zirconium wear-resistant filler.
[0012] S4: Weigh 60-75 parts by weight of fluorine-doped zirconium wear-resistant filler and add it to the silane coupling modification solution for reaction. After centrifugation, washing and drying, the fluorosilane modified filler is obtained.
[0013] S5: Weigh 15-25 parts by weight of flake-shaped hexagonal boron nitride, 3-8 parts by weight of vinyltriethoxysilane, 1-3 parts by weight of sodium bicarbonate and 80-95 parts by weight of anhydrous ethanol, stir under nitrogen protection at 90-110℃, cool and filter, wash and dry to obtain modified flake-shaped hexagonal boron nitride.
[0014] S6: By weight, 60-75 parts of fluorosilane modified filler, 15-25 parts of modified plate-shaped hexagonal boron nitride and 5-10 parts of fumed nano silica are mixed and ball-milled to obtain a composite filler. The composite filler is added to the base resin liquid of S1 to obtain a resin-filler mixture.
[0015] S7: By weight, add 0.2-0.8 parts camphorquinone, 0.5-1.2 parts ethyl 4-dimethylaminobenzoate, 0.3-0.6 parts diphenyliodonium hexafluorophosphate, 0.1-0.5 parts proanthocyanidin A2, and 0.05-0.2 parts β-carotene to the resin-filler mixture in sequence, and disperse to obtain the mixture.
[0016] S8: Vacuum degassing of the mixture and light-proof curing to obtain a wear-resistant dental resin composite material.
[0017] Preferably, S1 specifically involves: weighing 40-60 parts by weight of bisphenol A glycidyl methacrylate, 20-35 parts by weight of polyurethane dimethacrylate and 10-20 parts by weight of polyethylene glycol dimethacrylate, stirring at 300-600 r / min for 30-60 min under light-protected and nitrogen-protected conditions, adding 0.01-0.05 parts by weight of 2,2,6,6-tetramethylpiperidine-1-oxy free radical, and continuing to stir for 10-20 min to obtain the basic resin solution.
[0018] Preferably, S2 is specifically: by weight, 2-5 parts of tridecafluorooctyltrimethoxysilane and 95-98 parts of 75% ethanol aqueous solution are mixed, the pH is adjusted to 4.0-5.5 with acetic acid, and the mixture is mixed at 20-25℃ for 30-60 min to obtain silane coupling modified solution.
[0019] Preferably, S3 specifically comprises: weighing 30-45 parts by weight of zirconium oxychloride octahydrate, 0.5-3.5 parts by weight of sodium fluoride, 8-15 parts by weight of citric acid, 5-10 parts by weight of urea and 100-150 parts by weight of deionized water;
[0020] Citric acid and urea were added sequentially to deionized water and stirred at 25-40℃ and 200-400 r / min for 15-30 min. After stirring, zirconium oxychloride octahydrate was added at a rate of 0.5-3.0 g / min and stirring was continued for 20-40 min. After stirring was completed, sodium fluoride was added in 3-5 portions and stirring was continued for 30-60 min to obtain the precursor mixture.
[0021] The precursor mixture was subjected to a closed hydrothermal reaction at 160-200℃ for 12-24h. After the hydrothermal reaction was completed, it was naturally cooled to room temperature. The reaction product was taken out and centrifuged at 8000-12000r / min for 10-15min. The supernatant was discarded to obtain solid product A. Solid product A was washed with deionized water 3-5 times and then washed with anhydrous ethanol 2-3 times.
[0022] The washed solid product A was vacuum dried at 80-110℃ and -0.08MPa for 12-24h to obtain precursor powder. The powder was then placed in a muffle furnace and heated to 350-450℃ at a rate of 2-5℃ / min for 3-6h. After calcination, it was naturally cooled to room temperature to obtain fluorine-doped zirconium wear-resistant filler.
[0023] Preferably, S4 specifically involves: weighing 60-75 parts by weight of fluorine-doped zirconium wear-resistant filler and adding it to a silane coupling modification solution, stirring and refluxing at 60-80℃ and 200-400 r / min for 4-8 h. After the reaction is complete, centrifuging is used to separate the solid product B, which is washed 3-5 times with ethanol and vacuum dried at 80-100℃ and -0.098 MPa for 12-24 h to obtain the fluorosilane modified filler.
[0024] Preferably, S5 specifically involves: weighing 15-25 parts by weight of flake-shaped hexagonal boron nitride, 3-8 parts by weight of vinyltriethoxysilane, 1-3 parts by weight of sodium bicarbonate, and 80-95 parts by weight of anhydrous ethanol, stirring under nitrogen protection at 90-110°C for 6-12 hours, cooling to room temperature in the furnace, filtering through a 200-mesh filter, washing 3-5 times with acetone, and vacuum drying at 60-80°C and -0.07 MPa for 10-18 hours to obtain modified flake-shaped hexagonal boron nitride.
[0025] Preferably, S6 specifically involves: mixing 60-75 parts by weight of fluorosilane modified filler, 15-25 parts by weight of modified plate-like hexagonal boron nitride and 5-10 parts by weight of fumed nano-silica, adding the mixture to a planetary ball mill, using zirconia balls as grinding balls, and ball milling at 200-400 r / min for 2-4 h to obtain a composite filler. The composite filler is then added to the base resin liquid of S1 in 3-5 portions, and after each addition, it is dispersed at 1500-3000 r / min and ≤40℃ for 10-20 min to obtain a resin-filler mixture.
[0026] Preferably, S7 specifically involves: adding 0.2-0.8 parts of camphorquinone, 0.5-1.2 parts of ethyl 4-dimethylaminobenzoate, 0.3-0.6 parts of diphenyliodonium hexafluorophosphate, 0.1-0.5 parts of proanthocyanidin A2, and 0.05-0.2 parts of β-carotene to the resin-filler mixture by weight, and dispersing it at 1800-2600 r / min for 10-15 min to obtain the mixture.
[0027] Preferably, S8 specifically involves: transferring the mixture into a vacuum degassing machine, degassing it at -0.08 to -0.095 MPa for 30-60 minutes, and then curing it in a sealed environment at 25-30°C in the dark for 24-48 hours to obtain a wear-resistant dental resin composite material.
[0028] A wear-resistant dental resin composite material prepared according to the method described above.
[0029] Compared with the prior art, the beneficial effects of this invention are as follows:
[0030] 1. This invention significantly improves the interfacial stability and aging resistance of dental resin under combined environments of oral acidity, enzymatic hydrolysis, temperature cycling, and dynamic wear by synthesizing fluorine-doped zirconium wear-resistant filler and modifying the interface with tridecafluorooctyltrimethoxysilane. It solves the problem that the mechanical and wear-resistant properties of traditional filler-resin interfaces are easily penetrated by water, acidic hydrolysis, and enzymatic erosion, leading to rapid decline. Compared with the control example, the compressive strength decreased by 28.79% and the flexural strength decreased by 27.78% after 90 days of aging, the mechanical strength of the embodiment of this invention decreased by only 2-6%, and the interfacial bonding is strong.
[0031] 2. This invention employs a ternary synergistic compound of fluorine-doped zirconium wear-resistant filler, modified lamellar hexagonal boron nitride, and fumed nano-silica, simultaneously achieving a dual improvement in initial wear resistance and long-term wear stability, with an initial wear volume loss of only 4.2-5.1 × 10⁻⁶. -2 mm 3After 90 days of simulated oral aging, the wear increase was only 8.51-13.73%, which is far better than the 100% increase in the control case and the 81.25% increase in the control example. Under the dual effects of continuous chewing wear and strong acid corrosion, it still maintains a small amount of wear, effectively extending the service life of the restoration. Detailed Implementation
[0032] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0033] Example 1: This example provides a method for preparing a wear-resistant dental resin composite material, including the following steps:
[0034] S1: Weigh out 40 parts by weight of bisphenol A glycidyl methacrylate, 20 parts by weight of polyurethane dimethacrylate and 10 parts by weight of polyethylene glycol dimethacrylate (molecular weight 600). Stir at 300 r / min for 30 min under light protection and nitrogen protection. After stirring, add 0.01 parts of 2,2,6,6-tetramethylpiperidine-1-oxy free radical and continue stirring for 10 min to obtain the basic resin solution.
[0035] S2: By weight, mix 2 parts of tridecafluorooctyltrimethoxysilane and 95 parts of 75% ethanol aqueous solution, adjust the pH to 4.0-5.5 with acetic acid, and mix at 200 r / min for 30 min at 20℃ to obtain silane coupling modified solution;
[0036] S3: Weigh out 30 parts by weight of zirconium oxychloride octahydrate, 0.5 parts by weight of sodium fluoride, 8 parts by weight of citric acid, 5 parts by weight of urea and 100 parts by weight of deionized water.
[0037] Citric acid and urea were added sequentially to deionized water and stirred at 25°C and 200 r / min for 15 min. After stirring, zirconium oxychloride octahydrate was added at a rate of 0.5 g / min and stirring was continued for 20 min. After stirring was completed, sodium fluoride was added in three portions and stirring was continued for 30 min to obtain the precursor mixture.
[0038] The precursor mixture was subjected to a closed hydrothermal reaction at 160℃ for 12 hours (the precursor mixture was transferred to a polytetrafluoroethylene hydrothermal reactor with a filling degree of 70%, sealed, and placed in an oven for hydrothermal reaction). After the hydrothermal reaction was completed, the mixture was naturally cooled to room temperature. The reaction product was taken out and centrifuged at 8000 r / min for 10 min. The supernatant was discarded to obtain solid product A. Solid product A was first washed with deionized water 3 times and then washed with anhydrous ethanol 2 times.
[0039] The washed solid product A was vacuum dried at 80℃ and -0.08MPa for 12h to obtain precursor powder. The powder was then placed in a muffle furnace and heated to 350℃ at a rate of 2℃ / min for 3h. After calcination, it was naturally cooled to room temperature to obtain fluorine-doped zirconium wear-resistant filler.
[0040] S4: Weigh 60 parts by weight of fluorine-doped zirconium wear-resistant filler and add it to the silane coupling modification solution. Stir and reflux at 60℃ and 200r / min for 4h. After the reaction is completed, centrifuge to obtain solid product B, wash it 3 times with ethanol, and vacuum dry it at 80℃ and -0.098MPa for 12h to obtain fluorosilane modified filler.
[0041] S5: Weigh 15 parts by weight of plate-shaped hexagonal boron nitride (particle size 100nm), 3 parts by weight of vinyltriethoxysilane, 1 part by weight of sodium bicarbonate and 80 parts by weight of anhydrous ethanol. Stir at 90°C for 6 hours under nitrogen protection, cool to room temperature in the furnace, filter through a 200-mesh filter, wash 3 times with acetone, and vacuum dry at 60°C and -0.07MPa for 10 hours to obtain modified plate-shaped hexagonal boron nitride.
[0042] S6: By weight, 60 parts of fluorosilane modified filler, 15 parts of modified plate-like hexagonal boron nitride and 5 parts of fumed nano silica (particle size 10nm) are mixed and added to a planetary ball mill. Zirconia balls (diameter 5mm) are used as grinding balls and the mixture is ball-milled at 200r / min for 2h to obtain a composite filler. The composite filler is added to the base resin liquid of S1 in 3 portions. After each addition, the mixture is dispersed at 1500r / min and ≤40℃ for 10min to obtain a resin-filler mixture.
[0043] S7: By weight, add 0.2 parts camphorquinone, 0.5 parts ethyl 4-dimethylaminobenzoate, 0.3 parts diphenyliodonium hexafluorophosphate, 0.1 parts proanthocyanidin A2, and 0.05 parts β-carotene to the resin filler mixture in sequence, and disperse at 1800 r / min for 10 min to obtain the mixture.
[0044] S8: Transfer the mixture into a vacuum degassing machine and degas for 30 minutes at -0.08 MPa. After degassing, cure in a sealed environment at 25°C in the dark for 24 hours to obtain a wear-resistant dental resin composite material.
[0045] Example 2: This example provides a method for preparing a wear-resistant dental resin composite material, including the following steps:
[0046] S1: Weigh out 60 parts by weight of bisphenol A glycidyl methacrylate, 35 parts by weight of polyurethane dimethacrylate and 20 parts by weight of polyethylene glycol dimethacrylate (molecular weight 600). Stir at 600 r / min for 60 min under light protection and nitrogen protection. After stirring, add 0.05 parts of 2,2,6,6-tetramethylpiperidine-1-oxy free radical and continue stirring for 20 min to obtain the basic resin solution.
[0047] S2: By weight, 5 parts of tridecafluorooctyltrimethoxysilane and 98 parts of 75% ethanol aqueous solution are mixed, the pH is adjusted to 4.0-5.5 with acetic acid, and the mixture is mixed at 200 r / min for 60 min at 25℃ to obtain silane coupling modified solution;
[0048] S3: Weigh out 45 parts by weight of zirconium oxychloride octahydrate, 3.5 parts by weight of sodium fluoride, 15 parts by weight of citric acid, 10 parts by weight of urea and 150 parts by weight of deionized water.
[0049] Citric acid and urea were added sequentially to deionized water and stirred at 40℃ and 400r / min for 30min. After stirring, zirconium oxychloride octahydrate was added at a rate of 3.0g / min and stirring was continued for 40min. After stirring, sodium fluoride was added in 5 portions and stirring was continued for 60min to obtain the precursor mixture.
[0050] The precursor mixture was subjected to a closed hydrothermal reaction at 200℃ for 24 hours (the precursor mixture was transferred to a polytetrafluoroethylene hydrothermal reactor with a filling degree of 70%, sealed, and placed in an oven for hydrothermal reaction). After the hydrothermal reaction was completed, the mixture was naturally cooled to room temperature. The reaction product was taken out and centrifuged at 12000r / min for 15min. The supernatant was discarded to obtain solid product A. Solid product A was first washed with deionized water 5 times and then washed with anhydrous ethanol 3 times.
[0051] The washed solid product A was vacuum dried at 110℃ and -0.08MPa for 24h to obtain precursor powder. The powder was then placed in a muffle furnace and heated to 450℃ at a rate of 5℃ / min for 6h. After calcination, it was naturally cooled to room temperature to obtain fluorine-doped zirconium wear-resistant filler.
[0052] S4: Weigh 75 parts by weight of fluorine-doped zirconium wear-resistant filler and add it to the silane coupling modification solution. Stir and reflux at 80℃ and 400r / min for 8h. After the reaction is completed, centrifuge to obtain solid product B, wash with ethanol 5 times, and vacuum dry at 100℃ and -0.098MPa for 24h to obtain fluorosilane modified filler.
[0053] S5: Weigh 25 parts by weight of plate-shaped hexagonal boron nitride (particle size 100nm), 8 parts by weight of vinyltriethoxysilane, 3 parts by weight of sodium bicarbonate and 95 parts by weight of anhydrous ethanol. Stir at 110℃ for 12h under nitrogen protection, cool to room temperature in furnace, filter through a 200-mesh filter, wash 5 times with acetone, and vacuum dry at 80℃ and -0.07MPa for 18h to obtain modified plate-shaped hexagonal boron nitride.
[0054] S6: By weight, 75 parts of fluorosilane modified filler, 25 parts of modified plate-shaped hexagonal boron nitride and 10 parts of fumed nano silica (particle size 10nm) are mixed and added to a planetary ball mill. Zirconia balls (diameter 5mm) are used as grinding balls and the mixture is ball-milled at 400r / min for 4h to obtain a composite filler. The composite filler is added to the base resin liquid of S1 in 5 portions. After each addition, the mixture is dispersed at 3000r / min and ≤40℃ for 20min to obtain a resin-filler mixture.
[0055] S7: By weight, add 0.8 parts camphorquinone, 1.2 parts ethyl 4-dimethylaminobenzoate, 0.6 parts diphenyliodonium hexafluorophosphate, 0.5 parts proanthocyanidin A2, and 0.2 parts β-carotene to the resin filler mixture in sequence, and disperse at 2600 r / min for 15 min to obtain the mixture.
[0056] S8: Transfer the mixture into a vacuum degassing machine and degas at -0.095MPa for 60 minutes. After degassing, cure in a sealed environment at 30℃ in the dark for 48 hours to obtain a wear-resistant dental resin composite material.
[0057] Example 3: This example provides a method for preparing a wear-resistant dental resin composite material, including the following steps:
[0058] S1: Weigh out 53 parts by weight of bisphenol A glycidyl methacrylate, 29 parts by weight of polyurethane dimethacrylate and 17 parts by weight of polyethylene glycol dimethacrylate (molecular weight 600). Stir at 480 r / min for 46 min under light protection and nitrogen protection. After stirring, add 0.03 parts by weight of 2,2,6,6-tetramethylpiperidine-1-oxy free radical and continue stirring for 18 min to obtain the basic resin solution.
[0059] S2: By weight, 3.5 parts of tridecafluorooctyltrimethoxysilane and 97 parts of 75% ethanol aqueous solution are mixed, the pH is adjusted to 4.0-5.5 with acetic acid, and the mixture is mixed at 200 r / min for 47 min at 23℃ to obtain silane coupling modified solution;
[0060] S3: Weigh out 37 parts by weight of zirconium oxychloride octahydrate, 2.4 parts by weight of sodium fluoride, 12 parts by weight of citric acid, 7 parts by weight of urea and 120 parts by weight of deionized water.
[0061] Citric acid and urea were added sequentially to deionized water and stirred at 34℃ and 360r / min for 24min. After stirring, zirconium oxychloride octahydrate was added at a rate of 2.2g / min and stirring was continued for 37min. After stirring, sodium fluoride was added in 4 portions and stirring was continued for 55min to obtain the precursor mixture.
[0062] The precursor mixture was subjected to a closed hydrothermal reaction at 180℃ for 17 hours (the precursor mixture was transferred to a polytetrafluoroethylene hydrothermal reactor with a filling degree of 70%, sealed, and placed in an oven for hydrothermal reaction). After the hydrothermal reaction was completed, the mixture was naturally cooled to room temperature. The reaction product was taken out and centrifuged at 8000 r / min for 12 min. The supernatant was discarded to obtain solid product A. Solid product A was first washed with deionized water 3 times and then washed with anhydrous ethanol 2 times.
[0063] The washed solid product A was vacuum dried at 102℃ and -0.08MPa for 20h to obtain precursor powder. The powder was then placed in a muffle furnace and heated to 410℃ at a rate of 3℃ / min for 5h. After calcination, it was naturally cooled to room temperature to obtain fluorine-doped zirconium wear-resistant filler.
[0064] S4: Weigh 68 parts by weight of fluorine-doped zirconium wear-resistant filler and add it to the silane coupling modification solution. Stir and reflux at 73℃ and 330r / min for 6h. After the reaction is completed, centrifuge to obtain solid product B, wash with ethanol 5 times, and vacuum dry at 91℃ and -0.098MPa for 14h to obtain fluorosilane modified filler.
[0065] S5: By weight, 19 parts of flake-shaped hexagonal boron nitride (particle size 100 nm), 5.4 parts of vinyltriethoxysilane, 2.2 parts of sodium bicarbonate and 90 parts of anhydrous ethanol were weighed and stirred at 105 °C for 10 h under nitrogen protection. The mixture was then cooled to room temperature in the furnace, filtered through a 200-mesh filter, washed four times with acetone, and vacuum dried at 77 °C and -0.07 MPa for 15 h to obtain modified flake-shaped hexagonal boron nitride.
[0066] S6: By weight, 71 parts of fluorosilane modified filler, 21 parts of modified plate-like hexagonal boron nitride and 8 parts of fumed nano silica (particle size 10nm) are mixed and added to a planetary ball mill. Zirconia balls (diameter 5mm) are used as grinding balls and the mixture is ball-milled at 380r / min for 3h to obtain a composite filler. The composite filler is added to the base resin liquid of S1 in 4 portions. After each addition, the mixture is dispersed at 3000r / min and ≤40℃ for 17min to obtain a resin-filler mixture.
[0067] S7: By weight, add 0.5 parts camphorquinone, 0.8 parts ethyl 4-dimethylaminobenzoate, 0.4 parts diphenyliodonium hexafluorophosphate, 0.3 parts proanthocyanidin A2, and 0.11 parts β-carotene to the resin filler mixture in sequence, and disperse at 2600 r / min for 11 min to obtain the mixture.
[0068] S8: Transfer the mixture into a vacuum degassing machine and degas for 55 minutes at -0.095 MPa. After degassing, cure in a sealed environment at 30°C in the dark for 36 hours to obtain a wear-resistant dental resin composite material.
[0069] Comparative Example 1: The difference between this comparative example and Example 3 is that, in S3, zirconium oxychloride octahydrate is replaced with an equal mass of zirconium nitrate pentahydrate.
[0070] Comparative Example 2: The difference between this comparative example and Example 3 is that in S4, the mass of the fluorine-doped zirconium wear-resistant filler is increased to 90 parts.
[0071] Comparative Example 3: The difference between this comparative example and Example 3 is that vinyltriethoxysilane was not added in S5.
[0072] Preparation example: Curing of wear-resistant dental resin composite materials in the examples and comparative examples;
[0073] Use medical-grade polytetrafluoroethylene molding molds. Before use, wipe the inner wall of the mold three times with anhydrous ethanol and place it at room temperature to air dry for 15 minutes to remove oil and impurities from the inner wall.
[0074] A layer of medical-grade petroleum jelly release agent is evenly sprayed onto the inner wall of the mold cavity, with the spraying thickness controlled at 5μm. After spraying, the mold is left to stand for 10 minutes.
[0075] The wear-resistant dental resin composite material prepared by this invention is extracted using a disposable medical syringe. After removing the needle, it is injected into the mold cavity. After injection molding, the upper surface of the mold is smoothed with a flat polytetrafluoroethylene scraper to remove excess material.
[0076] After injection molding, the mold is placed in a room-temperature, light-proof, and dust-free environment and cured using a 465nm blue LED light curing machine. During curing, the light outlet of the curing machine is perpendicular to the mold surface, with a distance controlled at 10mm. The front of the mold is irradiated first, with a constant light intensity of 1000mW / cm². 2 Irradiation time is 30s; after the front side is cured, flip the mold and irradiate the back side of the mold with the same light intensity and distance for 30s; after irradiation, cool and demold.
[0077] Comparative example: The wear-resistant, low-shrinkage dental resin composite material prepared in Example 1 of Chinese Patent CN120227285B was selected.
[0078] Experimental Example 1: Detection of volume shrinkage rate;
[0079] (1) Clean the 10mL specific gravity bottle and glass stopper with anhydrous ethanol for 10min by ultrasonic cleaning, place them in a 60℃ drying oven for 2h, take them out and place them in a desiccator to cool to 25±1℃, weigh the empty specific gravity bottle + glass stopper, record it as m0, accurate to 0.0001g.
[0080] Pour 25°C distilled water into the specific gravity bottle until the liquid level is flush with the graduation mark on the neck of the bottle. Cover with a glass stopper (ensure there are no air bubbles inside the bottle and use filter paper to absorb the distilled water outside the bottle). Weigh the specific gravity bottle, glass stopper, and distilled water, and record the mass as m1, accurate to 0.0001g.
[0081] The density of distilled water at 25℃ is 0.99705 g / cm³. 3 Calculate the actual volume of the specific gravity bottle: V = (m1 - m0) / 0.99705, where V is in mL and accurate to 0.001 mL. Keep the calibration results for future reference.
[0082] (2) Take the calibrated empty specific gravity bottle + glass stopper, weigh the mass as m2 (same as the above steps), and place it in a constant temperature water bath at 25±1℃ for 10 min to preheat.
[0083] Under light-protected conditions, use a syringe to inject the degassed liquid resin sample into the preheated specific gravity bottle until the liquid level is flush with the neck mark. Cover with a glass stopper (ensuring no air bubbles inside the bottle and the resin outside the bottle is dried with filter paper), and place it again in a constant temperature water bath at 25±1℃ for 20 minutes.
[0084] Remove the specific gravity bottle, thoroughly dry the resin on the outer wall of the bottle and in the gaps of the glass stopper with filter paper, weigh the specific gravity bottle + glass stopper + liquid resin, and record it as m3, accurate to 0.0001g.
[0085] Calculate the density of liquid resin using the formula:
[0086]
[0087] Unit g / cm 3 Accurate to 0.0001 g / cm³ 3 The test was performed in parallel three times, and the arithmetic mean of the three results was taken.
[0088] (3) Weigh the sample prepared in the preparation example and record the mass of the sample in the air as m4, accurate to 0.0001g. Adjust the constant temperature water bath to 25±1℃, add 50mL of distilled water to a 100mL beaker, place it in the constant temperature water bath for 10min, wet the titanium alloy tweezers with distilled water, clamp the sample and immerse it in the constant temperature distilled water, weigh the mass of the sample immersed in the distilled water and record it as m5, accurate to 0.0001g.
[0089] Calculate the density of solid resin according to Archimedes' principle:
[0090] .
[0091] (4) , Substituting into the volume shrinkage rate formula, we can calculate VS (%), and the result should be rounded to two decimal places:
[0092] .
[0093] Experimental Example 2: Compressive strength (MPa) was tested according to YY / T 1026-2019 "Dental Science - Dental Amalgam".
[0094] Experimental Example 3: Flexural strength (MPa) was tested according to YY 1042-2011 "Polymer-based Restorative Materials in Dentistry".
[0095] Experimental Example 4: Volume loss (mm) was determined according to YY / T 0113-2015 "Test Method for Wear Resistance of Dental Composite Resins". 3 ).
[0096] Experiment Example 5: Oral Environment Simulation Experiment;
[0097] Preparation of basic simulation solution: Take 100 parts deionized water, 3 parts citric acid, 1.5 parts disodium hydrogen phosphate, 2 parts acetic acid, 0.8 parts sodium chloride, 0.2 parts potassium chloride, and 0.1 parts calcium chloride by mass fraction, stir until completely dissolved, store in a sealed container at 4℃, and preheat to 37±1℃ before use;
[0098] The preheated basal simulation solution was adjusted to pH 6.5 ± 0.1 using 0.5 mol / L sodium bicarbonate solution. Under this pH condition, 0.06 parts of salivary amylase (activity ≥ 3000 U / g) and 0.02 parts of lysozyme (activity ≥ 8000 U / g) were added, followed by Streptococcus mutans bacterial suspension (concentration 1 × 10⁻⁶). 920 portions of (CFU / mL) were thoroughly stirred and completely dissolved. The mixture was kept at this pH level for 2 hours. Then, the pH of the simulated solution was adjusted back to 2.5±0.1 with 0.5mol / L hydrochloric acid to obtain the oral simulated solution. The simulated solution was prepared according to the above steps each time it was changed, and the entire simulated solution was replaced every 24 hours.
[0099] The sample is fixed in a fixture, which is then immersed in a sealed reaction tank containing the oral cavity simulation liquid. The sample is completely submerged in the simulation liquid. The reaction tank is equipped with a constant temperature heating device to maintain the temperature of the simulation liquid in the tank at 37±1℃. The temperature is increased from 37℃ to 60℃ at a rate of 2℃ / min and held for 30min. Then, the temperature is decreased to 4℃ at a rate of 2℃ / min and held for 30min. This constitutes one temperature cycle, and one cycle is completed every hour.
[0100] Meanwhile, an 8mm diameter alumina grinding ball (hardness HV1800) was used as the grinding head. A vertical dynamic load of 20N was applied, and the grinding head made a reciprocating linear motion with a frequency of 60 times / min and a stroke of 10mm. It made contact with the sample surface for wear, and the grinding head was kept immersed in the oral cavity simulation fluid throughout the wear process.
[0101] During the simulation, the sample was taken out every 24 hours and ultrasonically cleaned with deionized water for 5 minutes (power 100W, frequency 40kHz) to remove the simulated liquid residue and wear debris adhering to the surface. The sample was then immersed in the newly replaced simulated liquid for subsequent simulations until the total duration of 90 days was completed.
[0102] The compressive strength, flexural strength, and volume loss of each sample that completed the oral environment simulation experiment were tested according to Experiment Examples 2-4.
[0103] The results are shown in the table below:
[0104]
[0105] As shown in the table above, the initial volume shrinkage rate of the wear-resistant dental resin composite materials prepared in Examples 1-3 was between 2.48% and 2.66%, which was generally low and fluctuated little. It was basically the same as the 2.56% of the control example and lower than the 4.89% of the control example 2. This indicates that the basic formula and preparation process of the present invention can effectively control the volume shrinkage during the resin curing process. However, the excessive addition of fluorine-doped zirconium wear-resistant filler in the control example 2 would significantly damage the compatibility between the resin matrix and the filler, resulting in a significant increase in the volume shrinkage rate.
[0106] The initial compressive strength of Examples 1-3 was 268.5-271.2 MPa and the flexural strength was 176.2-181.5 MPa. All mechanical properties were significantly higher than those of the control example and were also better than the three comparative examples overall. This shows that the composite filler formed by the present invention, which combines fluorine-doped zirconium wear-resistant filler, modified plate-like hexagonal boron nitride, and fumed nano-silica, can achieve good bonding with the base resin liquid and effectively improve the initial mechanical strength of the material. In contrast, Comparative Example 3 did not modify the hexagonal boron nitride with silane, and the insufficient bonding force between the filler and the resin interface was the main reason for the significant decrease in its mechanical properties.
[0107] The initial volume loss in Examples 1-3 was 4.2-5.1 × 10⁻⁶. -2 mm 3 The wear resistance of the composite filler prepared in this invention is much lower than that of Comparative Example 3 and the control example, indicating that the composite filler prepared in this invention has excellent initial wear resistance. The hardness of the fluorine-doped zirconium wear-resistant filler, the lubrication and friction reduction effect of the modified hexagonal boron nitride, and the reinforcement effect of nano-silica work synergistically to significantly reduce the wear of the material. In contrast, Comparative Example 3, due to the lack of modification of hexagonal boron nitride, could not fully exert its friction reduction effect, resulting in a decrease in initial wear resistance.
[0108] After 90 days of aging in a simulated oral environment, the compressive strength of Examples 1-3 remained at 255.5-258.1 MPa, a decrease of approximately 4.8% compared to the initial 268.5-271.2 MPa; the flexural strength remained at 168.4-173.5 MPa, a decrease of 2-6% compared to the initial 176.2-181.5 MPa. The overall mechanical properties showed a small and stable decrease, significantly better than the control example, whose compressive strength decreased from 243.1 MPa to 173.1 MPa (a decrease of 28.79%) and flexural strength decreased from 157.3 MPa to 113.6 MPa (a decrease of 27.78%). This was also significantly better than Comparative Examples 1 and 3, where Comparative Example 1 showed a 21.39% decrease in compressive strength and a 24.12% decrease in flexural strength, and Comparative Example 3... The compressive strength decreased by 10.48%; in Comparative Example 1, due to the replacement of the filler raw material, the acid corrosion resistance and hydrolysis resistance of the fluorine-doped zirconium wear-resistant filler decreased. Under the combined effects of acid, enzymatic hydrolysis and temperature cycling, the interface between the filler and the resin was rapidly destroyed, resulting in a significant decrease in mechanical properties; in Comparative Example 3, the unmodified hexagonal boron nitride was prone to interfacial separation in the simulated liquid, which also caused a significant decrease in compressive strength.
[0109] After 90 days of simulated oral cavity wear, the volume loss in Examples 1-3 was 4.9-5.8 × 10⁻⁶. -2 mm 3Compared to the initial value, the wear increase ranged from 8.51% to 13.73%, with a small wear amplitude and the material's wear-resistant structure remaining intact. Its long-term wear resistance stability was outstanding, far superior to the control example, with its volume loss decreasing from 7.8 × 10⁻⁶. 2 mm 3 Increased to 15.7 × 10⁻ 2 mm 3 The wear amount directly doubled, with an increase of 100%; it is also superior to Comparative Example 1 and Comparative Example 3, with an increase of 81.25% in Comparative Example 1, 19.30% in Comparative Example 3, and 27.27% in Comparative Example 2. This indicates that the wear-resistant dental resin composite material prepared by this invention can effectively maintain interface stability and the integrity of the wear-resistant structure in the complex acidic, enzymatic, temperature cycling, and dynamic wear environment of the oral cavity. The fluorosilane modification gives the filler excellent hydrophobicity and corrosion resistance, and the long-term wear reduction effect of the modified hexagonal boron nitride is also fully utilized.
[0110] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a wear-resistant dental resin composite material, characterized in that, Includes the following steps: S1: Weigh 40-60 parts by weight of bisphenol A glycidyl methacrylate, 20-35 parts by weight of polyurethane dimethacrylate and 10-20 parts by weight of polyethylene glycol dimethacrylate, stir under light-proof and nitrogen protection, add 0.01-0.05 parts by weight of 2,2,6,6-tetramethylpiperidine-1-oxy free radical, and continue stirring to obtain the base resin solution; S2: By weight, mix 2-5 parts of tridecafluorooctyltrimethoxysilane and 95-98 parts of ethanol aqueous solution, adjust the pH to 4.0-5.5, and mix to obtain silane coupling modified solution; S3: Weigh out 30-45 parts by weight of zirconium oxychloride octahydrate, 0.5-3.5 parts by weight of sodium fluoride, 8-15 parts by weight of citric acid, 5-10 parts by weight of urea and 100-150 parts by weight of deionized water. Citric acid and urea were added to deionized water in sequence and stirred. Zirconium oxychloride octahydrate was added and stirred. Sodium fluoride was added in 3-5 portions and stirred continuously to obtain the precursor mixture. The precursor mixture was subjected to a closed hydrothermal reaction at 160-200℃, cooled and centrifuged to obtain solid product A, washed and dried to obtain precursor powder, calcined at 350-450℃ and cooled to obtain fluorine-doped zirconium wear-resistant filler. S4: Weigh 60-75 parts by weight of fluorine-doped zirconium wear-resistant filler and add it to the silane coupling modification solution for reaction. After centrifugation, washing and drying, the fluorosilane modified filler is obtained. S5: Weigh 15-25 parts by weight of flake-shaped hexagonal boron nitride, 3-8 parts by weight of vinyltriethoxysilane, 1-3 parts by weight of sodium bicarbonate and 80-95 parts by weight of anhydrous ethanol, stir under nitrogen protection at 90-110℃, cool and filter, wash and dry to obtain modified flake-shaped hexagonal boron nitride. S6: By weight, 60-75 parts of fluorosilane modified filler, 15-25 parts of modified plate-shaped hexagonal boron nitride and 5-10 parts of fumed nano silica are mixed and ball-milled to obtain a composite filler. The composite filler is added to the base resin liquid of S1 to obtain a resin-filler mixture. S7: By weight, add 0.2-0.8 parts camphorquinone, 0.5-1.2 parts ethyl 4-dimethylaminobenzoate, 0.3-0.6 parts diphenyliodonium hexafluorophosphate, 0.1-0.5 parts proanthocyanidin A2, and 0.05-0.2 parts β-carotene to the resin-filler mixture in sequence, and disperse to obtain the mixture. S8: Vacuum degassing of the mixture and light-proof curing to obtain a wear-resistant dental resin composite material.
2. The method for preparing the wear-resistant dental resin composite material according to claim 1, characterized in that, S1 is specifically as follows: Weigh 40-60 parts by weight of bisphenol A glycidyl methacrylate, 20-35 parts by weight of polyurethane dimethacrylate and 10-20 parts by weight of polyethylene glycol dimethacrylate. Stir at 300-600 r / min for 30-60 min under light protection and nitrogen protection. After stirring, add 0.01-0.05 parts of 2,2,6,6-tetramethylpiperidine-1-oxy free radical and continue stirring for 10-20 min to obtain the basic resin solution.
3. The method for preparing the wear-resistant dental resin composite material according to claim 1, characterized in that, S2 is specifically prepared by mixing 2-5 parts by weight of tridecafluorooctyltrimethoxysilane and 95-98 parts by weight of 75% ethanol aqueous solution, adjusting the pH to 4.0-5.5 with acetic acid, and mixing at 20-25℃ for 30-60 min to obtain silane coupling modified solution.
4. The method for preparing the wear-resistant dental resin composite material according to claim 1, characterized in that, S3 specifically consists of: weighing 30-45 parts by weight of zirconium oxychloride octahydrate, 0.5-3.5 parts by weight of sodium fluoride, 8-15 parts by weight of citric acid, 5-10 parts by weight of urea, and 100-150 parts by weight of deionized water. Citric acid and urea were added sequentially to deionized water and stirred at 25-40℃ and 200-400 r / min for 15-30 min. After stirring, zirconium oxychloride octahydrate was added at a rate of 0.5-3.0 g / min and stirring was continued for 20-40 min. After stirring was completed, sodium fluoride was added in 3-5 portions and stirring was continued for 30-60 min to obtain the precursor mixture. The precursor mixture was subjected to a closed hydrothermal reaction at 160-200℃ for 12-24h. After the hydrothermal reaction was completed, it was naturally cooled to room temperature. The reaction product was taken out and centrifuged at 8000-12000r / min for 10-15min. The supernatant was discarded to obtain solid product A. Solid product A was washed with deionized water 3-5 times and then washed with anhydrous ethanol 2-3 times. The washed solid product A was vacuum dried at 80-110℃ and -0.08MPa for 12-24h to obtain precursor powder. The powder was then placed in a muffle furnace and heated to 350-450℃ at a rate of 2-5℃ / min for 3-6h. After calcination, it was naturally cooled to room temperature to obtain fluorine-doped zirconium wear-resistant filler.
5. The method for preparing the wear-resistant dental resin composite material according to claim 1, characterized in that, S4 is specifically as follows: Weigh 60-75 parts by weight of fluorine-doped zirconium wear-resistant filler and add it to the silane coupling modification solution. Stir and reflux at 60-80℃ and 200-400 r / min for 4-8 h. After the reaction is completed, centrifuge to obtain solid product B, wash with ethanol 3-5 times, and vacuum dry at 80-100℃ and -0.098 MPa for 12-24 h to obtain fluorosilane modified filler.
6. The method for preparing the wear-resistant dental resin composite material according to claim 1, characterized in that, Specifically, S5 is prepared by weighing 15-25 parts by weight of plate-shaped hexagonal boron nitride, 3-8 parts by weight of vinyltriethoxysilane, 1-3 parts by weight of sodium bicarbonate, and 80-95 parts by weight of anhydrous ethanol. The mixture is stirred at 90-110°C for 6-12 hours under nitrogen protection, cooled to room temperature in the furnace, filtered through a 200-mesh filter, washed 3-5 times with acetone, and vacuum dried at 60-80°C and -0.07 MPa for 10-18 hours to obtain modified plate-shaped hexagonal boron nitride.
7. The method for preparing the wear-resistant dental resin composite material according to claim 1, characterized in that, S6 is specifically made as follows: by weight, 60-75 parts of fluorosilane modified filler, 15-25 parts of modified plate-shaped hexagonal boron nitride and 5-10 parts of fumed nano silica are mixed and added to a planetary ball mill. Using zirconia balls as grinding balls, the mixture is ball-milled at 200-400 r / min for 2-4 h to obtain a composite filler. The composite filler is added to the base resin liquid of S1 in 3-5 portions. After each addition, the mixture is dispersed at 1500-3000 r / min and ≤40℃ for 10-20 min to obtain a resin-filler mixture.
8. The method for preparing the wear-resistant dental resin composite material according to claim 1, characterized in that, S7 specifically involves adding, by weight, 0.2-0.8 parts camphorquinone, 0.5-1.2 parts ethyl 4-dimethylaminobenzoate, 0.3-0.6 parts diphenyliodonium hexafluorophosphate, 0.1-0.5 parts proanthocyanidin A2, and 0.05-0.2 parts β-carotene to the resin-filler mixture in sequence, and dispersing at 1800-2600 r / min for 10-15 min to obtain the mixture.
9. The method for preparing the wear-resistant dental resin composite material according to claim 1, characterized in that, S8 specifically involves transferring the mixture into a vacuum degassing machine and degassing it for 30-60 minutes at -0.08 to -0.095 MPa. After degassing, the mixture is then cured in a sealed environment at 25-30°C in the dark for 24-48 hours to obtain a wear-resistant dental resin composite material.
10. A wear-resistant dental resin composite material prepared by the method according to any one of claims 1-9.
Citation Information
Patent Citations
Wear-resistant low-shrinkage dental resin composite material and preparation method thereof
CN120227285B